2020
DOI: 10.17085/apm.20021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of changes in anesthetic methods for cesarean delivery: an analysis for 5 years using the big data of the Korean Health Insurance Review and Assessment Service

Abstract: Background: As an anesthesia induced during cesarean section, spinal anesthesia is preferred over general and epidural anesthesia. This study aimed to review the trend of anesthetic methods for cesarean section based on data obtained from the Korean Health Insurance Review and Assessment Service from 2013 to 2018.Methods: The anesthetic methods were analyzed in 753,285 parturients who underwent a cesarean section in Korea from 2013 to 2018. We determined the association between each anesthetic method and hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…As such, we were concerned about the possibility of selection bias. Literature data on the relative proportions of anesthetic methods used for cesarean deliveries are available only from 2013 to 2018 [ 6 ]. Analysis thereof showed that the rate of spinal anesthesia increased from 40.0% in 2013 to 53.7% in 2018, while the opposite trend was observed in general anesthesia, which decreased from 37.1% in 2013 to 22.2% in 2018.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, we were concerned about the possibility of selection bias. Literature data on the relative proportions of anesthetic methods used for cesarean deliveries are available only from 2013 to 2018 [ 6 ]. Analysis thereof showed that the rate of spinal anesthesia increased from 40.0% in 2013 to 53.7% in 2018, while the opposite trend was observed in general anesthesia, which decreased from 37.1% in 2013 to 22.2% in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were malignancies (C00-97), diseases of the blood and blood-forming organs, immune-system disorders (D50-89), obstetric trauma causing rupture of the uterus (O71), and antepartum hemorrhage (O46). The anesthetic methods were categorized into general anesthesia (L1211, L1221), spinal anesthesia (L1213, L1223), and epidural anesthesia (L1214, L1224), based on a previous study reporting trends in anesthetic methods in Korea [ 6 ]. Cases in which the anesthetic method could not be verified were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Korea, approximately 28.8% of cesarean sections have been performed under general anesthesia over the past five years [35], but the rate of general anesthesia limited to the obese parturient group has not yet been reported. The rate of general anesthesia in Korea is significantly higher than that in Western countries [36].…”
Section: General Anesthesiamentioning
confidence: 99%